“Evaluación de la densidad de siembra y su efecto en el rendimiento del cultivo de almizcle (hibiscus abelmoschus L.) en cacatachi Región San Martín” - Vásquez Lozano, Alberto (2002)
With the intention of evaluating the density of sowing and its effect in the yield in the musk · culture (Hibiscus abelmoschus L), a test was made Completely in Blocks Randomizados with five (05), treatments and four (04), repetitions, on 1 found of Mr. Pedro Hidalgo Reátegui, located in km 12,5, wagon marginal Tarapoto north - Moyobamba, district of Cacatachi, region San Martín - Peru. Located geographically by the following coordinates: West longitude 76º 21. 55., South latitude 06º 29. 40. and a 295 altitude of msnm. lt was used five densities of sowing: T1 (0.50m X 0.50m), T2 (0.50m X 0.80m), T3 (0.50m X 1.00m), T4 (1.00m X 1.00m), T5 (1.00m X 1.50m), respectively. Originating seed of parcels handled by the Association of Churches Evangelicas Kechwas of the forest was used. The ground is characterized to present/display a Frank texture - 1 clay - Sandy, with a Ph of 7,9, an average percentage of organic matter (3.08%), fosforo available 17 ppm, interchangeable potassium O, 75 meq/100 g of ground, calcio+magnesio 12 me:q/1 OOg of ground. The place is characterized to present/display a tropical dry forest, with a precipitation annual average of 1,200mm and a temperature 25,7 average of ºC. The obtained results show that treatment T3 (0.50m X 1.00m), obtained the greater grain yield with 1.550 Kg/Ha, reporting a net benefit of 5.171,32 new suns and with a relation Benefit - Cost of 3,00 new s1,ms. Yield T1 (0.50m X 0.50m), registered the lowest yield with 3.266 Kg/Ha.